CRISP: An Inpatient Pediatric Curriculum for Family Medicine Residents Using Clinical Reasoning and Illness Scripts - Gayatri B. Madduri; Elizabeth L. Torwekar; Shaban Demirel; Megan Durham; Kimberlee I. Hauff; Rajat Kaul; Tristan Nichols; Noga L. Ravid; Mason A. Shaner; Caroline E. Rassbach (Association of American Medical Colleges, 2024)
Introduction Clinical reasoning enables safe patient care and is an important competency in medical education but can be challenging to teach. Illness scripts facilitate clinical reasoning but have not been used to create pediatric curricula. Methods We created CRISP (Clinical Reasoning with Illness Scripts in Pediatrics), a curriculum comprising four 1-hour learning sessions that deliberately incorporated clinical reasoning concepts and illness scripts to organize how four common chief complaints were taught to family medicine residents on inpatient pediatric rotations. We performed a multisite curriculum evaluation project over 6 months with family medicine residents at four institutions to assess whether the use of clinical reasoning concepts to structure CRISP was feasible and acceptable for learners and instructors and whether the use of illness scripts increased knowledge of four common pediatric chief complaints. Results For all learning sessions, family medicine residents and pediatric hospitalists agreed that CRISP's format was preferable to traditional didactic lectures. Pre-/posttest scores showed statistically significant increases in family medicine resident knowledge (respiratory distress [n = 42]: pretest, 72%, posttest, 92%; abdominal pain [n = 44]: pretest, 82%, posttest, 96%; acute febrile limp [n = 44]: pretest, 68%, posttest, 81%; well-appearing febrile infant [n = 42]: pretest, 58%, posttest, 73%; ps < .05). Discussion By using clinical reasoning concepts and illness script comparison to structure a pediatric curriculum, CRISP represents a novel instructional approach that can be used by pediatric hospitalists to increase family medicine resident knowledge about diagnoses associated with common pediatric chief complaints.